Environmental Representation and Social Ecology in the Bugis Folktale Bakka Maroe: An Ecocritical Study - Sri Wahyuni; Sumiyadi Sumiyadi; Yulianeta Yulianeta; Tedi Permadi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study addresses the limited ecological readings of Bugis folklore by examining environmental representation and social ecology in the folktale Bakka Maroe. The article aims to analyze how ecological meanings are constructed through narrative symbols, conflict, and cultural values in the tale. This study employs a qualitative interpretive text analysis supported by semi-structured interviews with five purposively selected informants familiar with Bugis oral tradition. The analysis is organized using Garrard’s ecocritical categories of wilderness, animals, apocalypse, dwelling, pollution, and social ecology. The findings show that Bakka Maroe represents nature as a morally charged and unstable space, animals as ambivalent ecological agents, ecological disruption as a cultural warning, settlement as an ecological-political mode of dwelling, pollution as both material and ethical violation, and social ecology as the entanglement of environmental crisis with hierarchy and power. The novelty of this study lies in its integrated reading of environmental representation, social ecology, and cultural wisdom in a Bugis folktale through Garrard’s ecocritical framework, which has not been specifically applied to Bakka Maroe in previous studies.